Landscapes of History in the Novels of Lawrence Norfolk - Nagy Ladislav (Prague Journal of English Studies, 2015)
This article deals with novels by Lawrence Norfolk which are read with a focus on their visual quality and the way they depict history. It is argued that Norfolk’s historical novels are unique in their portrayal of “landscapes of history”, large canvases in which individual characters play marginal, or a rather insignificant role. This approach distinguishes Norfolk from much of contemporary historical fiction, albeit at times this strategy might not be wholly satisfactory from a critical perspective. However, the article claims that Norfolk’s novels are intellectually inspiring since, similar to landscape, they invite a certain gaze, yet deny us the possibility of naming, of conceptualising. They provide readers with impressive vistas on history, which is seen as something too large to understand and penetrate. In this the novels are anti-humanistic. Individual characters (and their actions) are insignificant, or significant only to such an extent that they subscribe to some mythical framework, as Norfolk shows in, arguably, his best novel, In the Shape of a Boar (2000).